2004
DOI: 10.1126/science.1102722
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Sulfide-Mediated Prebiotic Formation of Peptides

Abstract: Almost all discussions of prebiotic chemistry assume that amino acids, nucleotides, and possibly other monomers were first formed on the Earth or brought to it in comets and meteorites, and then condensed nonenzymatically to form oligomeric products. However, attempts to demonstrate plausibly prebiotic polymerization reactions have met with limited success. We show that carbonyl sulfide (COS), a simple volcanic gas, brings about the formation of peptides from amino acids under mild conditions in aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
300
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(312 citation statements)
references
References 11 publications
6
300
0
6
Order By: Relevance
“…The formation of dipeptides could reasonably be considered a simple evolutionary step for prebiotic amino acids to undertake on the early Earth, for example, by the facile reaction between amino acids and carbonyl sulfide near volcanic sources (25). On the other hand, the step should also be expected to be stochastic in the distribution of homochiral and racemic peptide products.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of dipeptides could reasonably be considered a simple evolutionary step for prebiotic amino acids to undertake on the early Earth, for example, by the facile reaction between amino acids and carbonyl sulfide near volcanic sources (25). On the other hand, the step should also be expected to be stochastic in the distribution of homochiral and racemic peptide products.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonyl sulfide (COS) is a reactive compound that has been detected in volcanic gas and mineral ash (Rasmussen et al 1982), along with its chemical relatives, carbon disulfide and carbon dioxide. Leman et al (2004) found that if COS is present in an aqueous solution of amino acids, di-and tripeptides are synthesized with yields up to 80%. In a second paper, Leman et al (2006) reported that amino-acyl phosphate anhydrides up to 30% yields were synthesized in mixtures of amino acids, phosphate, and COS.…”
Section: Carbonyl Sulfide As a Plausible Prebiotic Condensing Agentmentioning
confidence: 99%
“…The most commonly cited potential prebiotic activations of stable amino acid derivatives lead to the formation of N −carboxyanhydrides of α-amino acids [12,30,40]. NCAs have several features that make them highly amenable to building a desirable prebiotic chemistry (i.e.…”
Section: The Modelmentioning
confidence: 99%